ANALISIS MANAJEMEN PERUBAHAN TERHADAP KINERJA ORGANISASI PADA PT SOLUSI BANGUN INDONESIA TBK - Ida Trigani; Wulan Aditya Putri; Lingga Yuliana (Jurnal Bisnis Terapan, 2021)
Abstract Cement is one of the building material commodities that has an important role in the smooth running of development, particularly in the construction sector. The purpose of this study was to find out how the influence of Change Management on Company Organizational Performance and to determine the Aspects of Organizational Performance and Organizational Performance which have a major influence based on the Analytic Network Process analysis. Respondents who were involved in the study were a research analysis and business owner with a material store business unit. The sampling technique used in this research was purposive sampling method. This research was a descriptive study and requires a model and analysis tools that are able to accommodatethe research. The analytical tool used in this research was the Analytic Network Process (ANP) method. With ANP, the study analyzed the value per cluster, the value of all nodes and the synthesis value of the change management cluster. The results showed that change management has an impact on organizational performance. In change management, leadership performance is one of the six dimensions that provide the most important impact and get the highest value. Whereas in organizational performance, task performance gets the highest score. Keywords: Change Management, Organizational Performance, Analytic Network Process